Singular beams with transverse electric and transverse magnetic fields - Fadeyeva, T.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
We have obtained the solutions of the paraxial wave equation in free space and
homogeneous media in the form of transverse electric (TE) and transverse magnetic
(TM) fields with Laguerre-Gaussian (LG) and Hermite-Gaussian (HG) modulation
functions. In contrast to the standard TE and TM beams we revealed that the axially
symmetric field of LG mode beams have local elliptical polarization, while axial
symmetry is totally broken down in the HG beams. The results obtained can be used for
matching the fields inside the uniaxial crystal and free space.